Diterpenes and antimicrobial activity of Gochnatia polymorpha, Gochnatia glutinosa and Gochnatia haumaniana - López, María Eugenia (2011)
Gochnaﬁa polymorpha (Gp) (Mutisieae, Coinpositae), known as“cambara" in Paraguay and “eandela” in Brazil, is used in folkmedicine to treat respiratory disorders. Decoctions of the bark areused for the treatment of sores and uleers.The hexane extract (HE)of Gp was analyzed by GC-MS. The main constituents werespinaeene, spathulenol, sitostero], stigmasterol, campesterol, B-arnyrin, lupeol, vitamin E, lupeol acetate, sitostenone, heptadecanol,phytol and eycloeucalenol. HE showed no activity against Escheri-chia colt‘ ATCC 25922, Staphiiococeus am-ens ATCC 25923, S.aureus (SAMS), Salmonella sp. Psendomonas aeruginosa orEnterobaeter sp. (BLEE). Diterpenes were not detected in the HEof Gp. On the other hand, the essential oil of G. glutinosa (Gg) andthe HE of both Gg and G. haamnniana (Gh) showed good activityagainst S. attreus 25923, S. nureus (SAMS) and R aeruginosa. Thefollowing diterpenes were identiﬁed in these plants: epyrnanoyloxide, kaur-16-ene, 3,13-epoxy-15,16 dinorlahdane and 3-ot-hy-droxy-manool in both essential oil and HE from Gg, while kauran-16-ol, kaur-16-en-3-ol and kauran-19-oic-acid methyl ester were-identiﬁed in Gh.These results suggest that the antibacterial activ-ity could be related to the presence of diterpenes.